Legal Analysis of Return Orders Not Delivered to Destination by Couriers from the Perspective of the Compilation of Sharia Economic Law (Case Study in Tanjung Pura District) - Nurhidayati, Nurhidayati; Hasanah, Uswatun (Universitas Islam Sultan Agung, 2024)
In e-commerce transactions in the marketplace application, courier obligations must be ensured to be realized properly, the issue of returning goods (return) in the world of e-commerce is not uncommon. Researchers found a situation where the return occurred because the ordered goods were not delivered to the destination by the courier, and asked the buyer to pick up the order himself, the buyer who did not agree to cause the ordered goods to be returned back to the seller, so the research with the title